Game-based Learning in Indonesian Language Instruction: A Qualitative Study of Student Engagement and Cultural Integration at an Islamic Elementary School - Nadia Rafika Ayu; Marisa Noprianti; Nova Asvio; Betti Dian Wahyuni; Heny Friantary (PPSDP International Journal of Education, 2026)
This qualitative study examines the implementation of Game-Based Learning (GBL) in Indonesian language instruction at a third-grade classroom of an integrated Islamic elementary school in Bengkulu City, Indonesia. The research addressed low student engagement and limited concentration on text- and grammar-based materials. Data were collected through classroom observations (six sessions), semi-structured interviews (eight students, one teacher, one principal), and documentation over one semester. Findings reveal that GBL transformed passive learning into active, participatory experiences. Specific games Word Detective (vocabulary and sentence construction), Character Bingo (listening comprehension using the Malin Kundang folktale), and Sentence Dice (creative writing) enhanced behavioral, emotional, and cognitive engagement. Students reported increased motivation (seven of eight students), confidence (six of eight), and collaboration. The teacher’s role shifted from knowledge transmitter to facilitator, creating an inclusive, psychologically safe environment. A “Star Points” gamification system fostered healthy competition and collective responsibility. This study contributes empirical evidence on integrating local cultural content into GBL, demonstrating that well-designed game-based activities can serve as natural classroom management strategies while supporting holistic language development. We recommend that primary teachers adopt structured, curriculum-aligned GBL approaches and that future research examine GBL across multiple schools and age groups using mixed methods.